2015
DOI: 10.1111/eje.12178
|View full text |Cite
|
Sign up to set email alerts
|

Developing students’ clinical reasoning skills: correlates of perceived relevance of two teaching and learning approaches

Abstract: The results suggest that students' perceptions of the relevance of the instructional design may be enhanced when outcomes, teaching, learning and assessment are constructively aligned during the development of clinical reasoning skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
1
4
0
1
Order By: Relevance
“…Quantitatively, most of the students completely agreed with CBL as a tool for scientific content assimilation (89.3%); completely agreed with the relevance of the presented cases (87.5%); and completely agreed with the use of case discussion for improving scientific knowledge (87.5%). These outcomes confirm previous findings demonstrating that CBL outperformed lecture‐based teaching (LBT) when it comes to perceiving the relevance of teaching and learning among students 19,20 . Specific findings even recommend the inclusion of CBL in the curriculum of oral medicine in face of its higher effectiveness over LBT 20 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Quantitatively, most of the students completely agreed with CBL as a tool for scientific content assimilation (89.3%); completely agreed with the relevance of the presented cases (87.5%); and completely agreed with the use of case discussion for improving scientific knowledge (87.5%). These outcomes confirm previous findings demonstrating that CBL outperformed lecture‐based teaching (LBT) when it comes to perceiving the relevance of teaching and learning among students 19,20 . Specific findings even recommend the inclusion of CBL in the curriculum of oral medicine in face of its higher effectiveness over LBT 20 .…”
Section: Discussionsupporting
confidence: 85%
“…These outcomes confirm previous findings demonstrating that CBL outperformed lecture-based teaching (LBT) when it comes to perceiving the relevance of teaching and learning among students. 19,20 Specific findings even recommend the inclusion of CBL in the curriculum of oral medicine in face of its higher effectiveness over LBT. 20 Because of the close interface between oral medicine/surgery and image-based diagnosis in oral radiology (addressed in the present study), such previous findings corroborate the present study on CBL as a useful tool for education at the dental undergraduate level.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that teaching methodologies using CBL and/or PBL is positively related to the development of skills in dental practice 22,23 . Postma and White found a positive association in the students' perception on the relevance of different teaching-learning approaches as they were exposed to a CBL methodology 20 .…”
Section: Discussionmentioning
confidence: 98%
“…Other studies 10,12 also found similar results for training areas related to orofacial pain and administration/management tasks. Critical thinking and problem-solving skills are essential components of the vocational training, whereas in the conventional training (e.g., explanatory class) the content transmission is passive as the student's experience is not enhanced and there is neither integration of different disciplines 17 nor autonomy, thus making the learning process fully dependent on the faculty member 20 . Diversified teachinglearning practices are needed to enhance human resource training in healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…No segundo caso, a maioria dos estudantes alegou não saber tratar clinicamente esses pacientes por causa de sua condição sistêmica enfraquecida. Curiosamente, outros estudos já mostraram que a percepção do estudante em odontologia em geral é que eles não estão adequadamente preparados para se comunicar com os pacientes 8,9 .…”
Section: Discussionunclassified